Recurrent liposarcoma surgery of upper extremity - A. S. Samoylov; Yu. D. Udalov; S. E. Voskanyan; N. G. Stepanyants; A. V. Aksenenko; G. A. Baksiyan; D. N. Astakhov; M. Sh. Zugumova (Исследования и практика в медицине)
Your attention is given to the clinical observation of a patient with recurrent liposarcoma of the left upper limb. According to vital indications with palliative purpose, the patient underwent surgery in the Oncology Department of surgical methods of treatment of FSBI SSC FMBC named after A.I. Burnazyan, FMBA of Russia. The operation was carried out in the amount of interscapularthoracic amputation on the left with resection of the left clavicle, plasty of the defect of rotary musclefat flap on a vascular pedicle after previous surgical treatment previous year in the amount of assertional the left upper extremity with the plastic of the wound defect myofascial flap on a vascular pedicle. Attempts to palliative embolization of blood vessels supplying the tumor node were unsuccessful, and the only option to provide medical care at this stage was surgical treatment. It should also be noted that the patient has a history of cancer of the left breast, in connection with which she was treated about 10 years ago. Currently, the patient is under our dynamic control and is undergoing adjuvant radiotherapy. The postoperative period was uneventful.